2018
DOI: 10.1088/1674-1056/27/10/108501
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of total ionizing dose on single event effect induced by pulsed laser microbeam on SiGe heterojunction bipolar transistor

Abstract: The synergistic effect of total ionizing dose (TID) on single event effect (SEE) in SiGe heterojunction bipolar transistor (HBT) is investigated in a series of experiments. The SiGe HBTs after being exposed to 60 Co γ irradiation are struck by pulsed laser to simulate SEE. The SEE transient currents and collected charges of the un-irradiated device are compared with those of the devices which are irradiated at high and low dose rate with various biases. The results show that the SEE damage to un-irradiated dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In order to make the device run as close as possible to the actual radiation environment, it is important to study the effects of 60 Co γ and proton irradiation on the device. [31,32] Thus, in order to simulate real-life conditions that devices may encounter when operating in space radiation environments, investigations are performed by using both the Northwest Institute of Nuclear Technology 60 Co γ radiation source and XiPAF.…”
Section: Mev Proton Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to make the device run as close as possible to the actual radiation environment, it is important to study the effects of 60 Co γ and proton irradiation on the device. [31,32] Thus, in order to simulate real-life conditions that devices may encounter when operating in space radiation environments, investigations are performed by using both the Northwest Institute of Nuclear Technology 60 Co γ radiation source and XiPAF.…”
Section: Mev Proton Setsmentioning
confidence: 99%
“…[34] Moreover, during 60 Co γ radiation, an electric field pointing from collector to base is formed at the B/C junction by the cut-off bias so that the ionized holes transit towards the base side in the LOCOS (Location Oxidation of Silicon) and generate stable positive oxide-trap charges near the base, forming space electric field. While the SEE of the SiGe HBT device is studied by using 100-MeV proton, this space electric field whose direction is from base to collector diminishes the applied voltage of V C = 5 V. [31] Thereby, this is also the main reason why the peak value of the collector transient current decreases with the cumulation dose increasing.…”
Section: Mev Proton Setsmentioning
confidence: 99%
“…Therefore, lasers of different wavelengths (1064 nm and 532 nm) and incident energy were used to study the collector transient current peak, cur-rent duration and charge collection under different applied bias conditions. [11,12] Finally, the equivalent linear energy transfer (LET) value relationship between the pulsed laser and the heavy ions was established by carrying out technology computer-aided design (TCAD) simulations. The single event transient induced by heavy-ion incidence was also studied.…”
Section: Introductionmentioning
confidence: 99%
“…A model PL2210 picosecond laser with a pulse width of 21.8 ps, a lens with a numerical aperture of 0.7 and an oscilloscope with a bandwidth of 12.5 GHz and sample rate of 50 gigasamples•s −1 were used. [11] The laser can provide infrared light with a photon energy of 1.17 eV (wavelength 1064 nm) and a frequency-doubled green light component of 2.32 eV (wavelength 532 nm) [7] , both of which are Gaussian beams. The incident depths of the 1064 nm and 532 nm wavelength lasers were about 500 µm and 2 µm, respectively.…”
Section: Sample Introductionmentioning
confidence: 99%
“…Although silicon-on-insulator (SOI) technology is helpful for improving the tolerance of devices to SET, the sensitivity of SOI device to TID is also serious due to the existence of oxide insulator [7][8][9]. Therefore, electronics devices for space environments experience TID and SET simultaneously [10][11][12][13]. Some simulation and experimental results have indicated that the SET pulse width and the sensitive area decrease due to heavy-ion induced dose for the IBM 180nm process [10].…”
Section: Introductionmentioning
confidence: 99%